Ethical Issues in Building and Maintaining Coalitions: A 10-Step Decision-Making Model for Choosing between Right and Right - Martie Gillen; Carolyn S. Wilken; Katey Walker (EDIS)
Coalitions form in communities to address complex issues and to take advantage of the resources and expertise of diverse people and groups. Sometimes coalitions may face difficult ethical dilemmas, and it helps for all members of the coalition to be aware of these issues. Learn about the 10-Step Decision-Making Model to use when making ethical decisions. This revised 8-page fact sheet was written by Martie Gillen, Carolyn S. Wilken, and Katey Walker, and published by the UF Department of Family, Youth, and Community Sciences, August 2012.